A140 OUTCOMES OF ENDOSCOPIC ABLATIVE THERAPY AND SURGICAL MANAGEMENT IN BARRETT'S ESOPHAGUS: DEVELOPMENT OF A MULTIDISCIPLINARY DATABASE. (4th March 2021) - Wilson, H A; Blakely, P; Sun, W; Dang, J; Karmali, S; Wong, C
Abstract: Background: Barrett's Esophagus (BE) is a precancerous condition in which epithelial cells of the esophagus undergo metaplasia from stratified squamous to simple columnar. This metaplasia predisposes the epithelial cells to a stepwise progression of dysplasia, and ultimately esophageal adenocarcinoma. The risk for developing malignancy increases with greater degrees of dysplasia; therefore, current intervention is focused on reducing the incidence and progression of dysplasia. There is good evidence that endoscopic therapies, such as resection and ablation, are effective at treating dysplasia in BE; however, the optimal modality to reduce recurrence is unclear. While proton pump inhibitors (PPI) remain the mainstay of medical treatment, fundoplication may be indicated for failure of medical therapy and patients with anatomical defects such as hiatal hernias. There is currently a lack of guidelines for optimal combined medical and surgical treatment for patients with BE who have received endoscopic treatment. Aims: Our aim is to create a novel multidisciplinary database of endoscopically treated patients with BE that will allow us to monitor long-term outcomes and disease progression. Methods: A systematic review on the impact of fundoplication on the progression of BE to dysphagia and adenocarcinoma is underway. Using an existing database as a foundation, we developed a prospective database of patients with BE using RedCAP, a secure cloud-based database. Feedback from specialists in both Gastroenterology and General Surgery contributed to a database that is to our knowledge, the first to combine medicine and surgery. Results: As proof of concept, we entered seven participants' information into the database. The majority of participants had risk factors for BE, including caucasian ethnicity, male gender, age > 50 years, and elevated BMI. Five came from the endoscopic ablation program and two were referred by surgery. Four patients underwent laparoscopic Nissen fundoplication, of which three had concurrent hiatal hernia repairs. Two have been seen for post-surgical surveillance. One remained dysplasia free PPI dose was reduced. The other demonstrated a reduction of BE, but continued the same dose of PPI and is scheduled to receive ablation therapy. Conclusions: Our preliminary results indicate our database can successfully monitor both medical and surgical parameters of patients with BE. With additional participants and longitudinal data, we are positioned to provide evidence-based guidelines to treat and monitor endoscopically treated patients with BE from both a medical and surgical perspective. Funding Agencies: None